Time-dependent angular analysis of the decay B0s → J/ψφ and extraction of ΔΓs and the CP-violating weak phase φs by ATLAS - Alonso, Francisco (2012)
A measurement of B0s → J/ψϕ decay parameters, including the CP-violating weak phase ϕs and the decay width difference ΔΓs is reported, using 4.9 fb−1 of integrated luminosity collected in 2011 by the ATLAS detector from LHC pp collisions at a centre-of-mass energy √s = 7 TeV. The mean decay width Γs and the transversity amplitudes |A0(0)|2 and |A∥(0)|2 are also measured. The values reported for these parameters are: ϕs = 0.22 ± 0.41 (stat.) ± 0.10 (syst.) rad ΔΓs = 0.053 ± 0.021 (stat.) ± 0.010 (syst.) ps−1 Γs = 0.677 ± 0.007 (stat.) ± 0.004 (syst.) ps−1 |A0(0)|2 = 0.528 ± 0.006 (stat.) ± 0.009 (syst.) |A∥(0)|2 = 0.220 ± 0.008 (stat.) ± 0.007 (syst.) where the values quoted for ϕs and ΔΓs correspond to the solution compatible with the external measurements to which the strong phase δ⊥ is constrained and where ΔΓs is constrained to be positive. The fraction of S-wave KK or f0 contamination through the decays Bsup>0s → J/ψK+K− (f0) is measured as well and is found to be consistent with zero. Results for ϕs and ΔΓs are also presented as 68%, 90% and 95% likelihood contours, which show agreement with Standard Model expectations.